Between Earth and Sky - Stanisheva, Maria (United States, 2012)
This documentary explores a Native American family’s struggle against cancer and cultural extinction as money becomes increasingly valued.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films